2019
DOI: 10.1212/wnl.0000000000006748
|View full text |Cite
|
Sign up to set email alerts
|

Atrial cardiopathy in patients with embolic strokes of unknown source and other stroke etiologies

Abstract: ObjectiveTo investigate the prevalence and clinical determinants of atrial cardiopathy in patients with embolic stroke of unknown source (ESUS) and compare with other established stroke etiologies.MethodsIn a cross-sectional study of 846 consecutive patients with ischemic stroke, we compared the prevalence of atrial cardiopathy (defined by p-wave terminal force in V1 >5,000 µV·ms or severe left atrial enlargement) between ESUS patients and patients with large artery atherosclerosis (LAA) and small vessel di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 31 publications
4
33
0
1
Order By: Relevance
“…These prior studies did not use the ESUS definition, which ensures uniform evaluation of potential etiologies, and did not include continuous heart‐rhythm monitoring to rule out underlying AF, which may be involved in the relationship between left atrial size and stroke. A recent study found no significant difference in left atrial enlargement in ESUS patients versus non‐cardioembolic stroke patients, but this study was likely underpowered based on its reported confidence intervals . In this context, our study provides novel information about the relationship between left atrial size and ischemic stroke risk, suggesting that left atrial structural derangements may play a pathogenic role in strokes that are currently labeled as being of undetermined source.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These prior studies did not use the ESUS definition, which ensures uniform evaluation of potential etiologies, and did not include continuous heart‐rhythm monitoring to rule out underlying AF, which may be involved in the relationship between left atrial size and stroke. A recent study found no significant difference in left atrial enlargement in ESUS patients versus non‐cardioembolic stroke patients, but this study was likely underpowered based on its reported confidence intervals . In this context, our study provides novel information about the relationship between left atrial size and ischemic stroke risk, suggesting that left atrial structural derangements may play a pathogenic role in strokes that are currently labeled as being of undetermined source.…”
Section: Discussionmentioning
confidence: 75%
“…Several markers of abnormal atrial anatomy and function have been associated with ischemic stroke independently of AF . Left atrial volume is a core feature of atrial cardiopathy but the relationship between left atrial volume and ESUS remains unclear given conflicting results from prior studies . If atrial cardiopathy is an under‐recognized risk factor for ESUS, it should be more prevalent among ESUS cases than strokes of known non‐cardioembolic etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse current publications point to the notion that at least a proportion of ESUS patients display similarities with patients with cardioembolism, e.g., in regard to risk for stroke recurrence or thrombus histology [22,40,41]. Hypothetically, a part of ESUS may be due to embolism based on atrial cardiopathy even beyond AF, which may basically be interpreted as a symptom at the end stage of this pathology [42,43]. Thus, further research to elucidate the mechanisms behind ESUS and its linkage to atrial cardiopathy is highly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this mechanism, a recent study demonstrated that the prevalence of atrial cardiopathy, as assessed by ECG markers and LA dilation, was higher in ESUS patients compared with noncardioembolic stroke patients (26.6% in ESUS vs. 12.1% in LAA vs. 16.9% in SVD). 38 Certain limitations of the present report need to be acknowledged. First, the case-control design does not allow us to confirm causative associations between the measured markers.…”
Section: Arterial Stiffness and Left Atrial Function In Esusmentioning
confidence: 82%